Білім мен ғылымды жан əлемімен дарытқан тұлға, аяулы ғалым-ұстаз, профессор Г.Ш. Жамбатырованың рухына арналады (International relations and international law Journal, 2016)
Посвящается человеку, всей душой посвятившему себя знаниям и науке, незаменимому наставнику и ученому, профессору Г.Ш. ЖамбатыровойIt is devoted to the person who with all the heart has devoted himself to knowledge and science, the irreplaceable mentor and the scientist, professor G. Sh. Zhambatyrova